2009
DOI: 10.1101/gad.1773909
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid signaling pathways increase stability of Small Heterodimer Partner (SHP) by inhibiting ubiquitin–proteasomal degradation

Abstract: Small Heterodimer Partner (SHP) inhibits activities of numerous transcription factors involved in diverse biological pathways. As an important metabolic regulator, SHP plays a key role in maintaining cholesterol and bile acid homeostasis by inhibiting cholesterol conversion to bile acids. While SHP gene induction by increased bile acids is well established, whether SHP activity is also modulated remains unknown. Here, we report surprising findings that SHP is a rapidly degraded protein via the ubiquitin-protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 31 publications
8
116
1
Order By: Relevance
“…In the absence of MG132, the levels of ubiquitinated FLAG-SHP WT and FLAG-SHP R38H were similar that were enhanced by MG132 treatment (Fig. 4B), consistent with the report in Hepa1c cells (32). On the contrary, the p.K170N mutation robustly increased ubiquitinated FLAG-SHP K170N , as indicated by the ladder of high molecular weight forms of FLAG- , suggesting that the Lys to Asn conversion at 170 position made FLAG-SHP K170N more susceptible to proteasomal degradation, which may contribute to its down-regulation.…”
Section: Regionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the absence of MG132, the levels of ubiquitinated FLAG-SHP WT and FLAG-SHP R38H were similar that were enhanced by MG132 treatment (Fig. 4B), consistent with the report in Hepa1c cells (32). On the contrary, the p.K170N mutation robustly increased ubiquitinated FLAG-SHP K170N , as indicated by the ladder of high molecular weight forms of FLAG- , suggesting that the Lys to Asn conversion at 170 position made FLAG-SHP K170N more susceptible to proteasomal degradation, which may contribute to its down-regulation.…”
Section: Regionsupporting
confidence: 81%
“…1C). Although Lys-170 was not identified as a major ubiquitination site in a recent study (32), it remains an interesting question if Lys-170 plays a role in SHP protein ubiquitination and if p.K170N mutation alters such process. The antibodies against the FLAG tag produced nonspecific bands in Hepa-1 cells (Fig.…”
Section: Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many potential mechanisms by which PKC␤ either indirectly or directly can affect hepatic CYP7A1 transcription. First, p42/44 MAPK activation has been linked with CYP7A1 suppression by both SHP-dependent and SHP-independent pathways (44,45). One such study has shown that p42/44 MAPK -induced phosphorylation of hepatic SHP at serine 26 stabilizes this protein by inhibiting ubiquitin-proteasomal degradation (45).…”
Section: Discussionmentioning
confidence: 99%
“…SHP acts as a corepressor of liver receptor homolog 1 (LRH-1/NR5A2)-or hepatocyte nuclear factor 4 ␣ (HNF4 ␣ /NR2A1)-induced transcription of Cyp7a1 and Cyp8b1 ( 14,18,(21)(22)(23). On the other hand, FGF15/19 activates its receptor FGFR4 located on the plasma membrane of hepatocytes, which leads to the inhibition of Cyp7a1 and Cyp8b1 expression either via SHP by substantially increasing the stability of SHP protein or by SHP-independent means ( 19,20,(24)(25)(26)(27). To better defi ne the role of FXR, we determined the effect of three potent and selective, synthetic FXR agonists (RO5186026, the X-Ceptor compound, and GW4064) and one less potent and less selective BA derivative (6-ECDCA, INT-747) on BA and cholesterol metabolism in mice and hamsters.…”
Section: Journal Of Lipid Research Volume 54 2013mentioning
confidence: 99%